131I‐MIBG followed by consolidation with busulfan, melphalan and autologous stem cell transplantation for refractory neuroblastoma1. Issue 5 (28th September 2012) - French, Sarah; DuBois, Steven G.; Horn, Biljana; Granger, Meaghan; Hawkins, Randall; Pass, Amy; Plummer, Ellen; Matthay, Katherine
Abstract Background 131I‐metaiodobenzylguanidine (MIBG) produces a 37% response rate in relapsed/refractory neuroblastoma, and could be used to improve remission status prior to myeloablative chemotherapy with autologous stem cell transplant (ASCT). The purpose of our report was to evaluate safety and response with MIBG therapy followed by myeloablative busulfan and melphalan (BuMel) with ASCT in patients with refractory neuroblastoma. Methods Retrospective chart review was done on patients treated with MIBG (18 mCi/kg) on Day 1 and ASCT on Day 14. Six to eight weeks after MIBG, patients without progressive disease received IV busulfan on Days −6 to −2 (target Css 700–900), melphalan (140 mg/m2 IV) on Day −1, and ASCT on Day 0. Response and toxicity were evaluated after MIBG and again after myeloablative therapy. Results Eight patients completed MIBG/ASCT followed by BuMel/ASCT. MIBG was well tolerated, with Grade 3 or 4 non‐hematologic toxicity limited to one patient with sepsis. Grade 3 mucositis occurred in six patients after BuMel/ASCT. One patient developed sinusoidal obstructive syndrome (SOS) and died 50 days post‐ASCT following myeloablative conditioning. All patients engrafted neutrophils (median 16.5 days) and platelets (median 32 days) after BuMel, excluding the patient with SOS. After all therapy, there were three complete, two partial, and one minor response in seven evaluable patients. Conclusions MIBG at doses up to 18 mCi/kg can be safely administered 6 weeks prior to a BuMel consolidative regimen for refractory neuroblastoma. Preceding MIBG did not impair engraftment following BuMel. This regimen is being further evaluated in a Children's Oncology Group (COG) trial. Pediatr Blood Cancer 2013; 60: 879–884. © 2012 Wiley Periodicals, Inc.